Design, synthesis and biological evaluation of 2-pyrrolone derivatives as radioprotectors. (1st August 2022) - Satoh, Hidetoshi; Ochi, Shintaro; Mizuno, Kosuke; Saga, Yutaka; Ujita, Shohei; Toyoda, Miyu; Nishiyama, Yuichi; Tada, Kasumi; Matsushita, Yosuke; Deguchi, Yuichi; Suzuki, Keiji; Tanaka, Yoshimasa; et al.
Graphical abstract: Abstract: It is known that p53 is an important transcription factor and plays a central role in ionizing radiation (IR)-induced DNA damage responses such as cell cycle arrest, DNA repair and apoptosis. We previously reported that regulating p53 protein is an effective strategy for modulating cell fate by reducing the acute side effects of radiation therapy. Herein, we report on the discovery of STK160830 as a new radioprotector from a chemical library at The University of Tokyo and the design, synthesis and biological evaluation of its derivatives. The radioprotective activity of STK160830 itself and its derivatives that were synthesized in this work was evaluated using a leukemia cell line, MOLT-4 cells as a model of normal cells that express the p53 protein in a structure–activity relationships (SAR) study. The experimental results suggest that a direct relationship exists between the inhibitory effect of these STK160830 derivatives on the expression level of p53 and their radioprotective activity and that the suppression of p53 by STK160830 derivatives contribute to protecting MOLT-4 cells from apoptosis that is induced by exposure to radiation.